An end-to-end model framework for understanding and predicting changes in Antarctic marine ecosystems - Ilari Stollberg; Sophie Bestley; Andrew Constable; Elizabeth A. Fulton; Javier Porobic; David Green; Denise O’Sullivan; Mao Mori; Stuart Corney; Michael Sumner; Jessica Melbourne-Thomas (Ecological Modelling, 2026)

Seasonal diversity & behaviour of internal tidal bores revealed by year-long direct monitoring within a submarine canyon: Implications for particulate transport - Morgan T. Wolfe; Michael A. Clare; Esther J. Sumner; Veerle A.I. Huvenne; Rob A. Hall; Ian A. Kane (Earth and Planetary Science Letters, 2026)

Correction: Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2026)

Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract

Challenging the Standard Immunogenicity Assessment Approach: 1-Tiered ADA Testing Strategy in Clinical Trials - Ching-Ha Lai; Mu Chen; Sasha Fraser; Jessica Wang; Sean McAfee; Emma Speaks; Nicholas Simeone; Jacqueline Rodriguez; Colin Stefan; Lisa DeStefano; Chinnasamy Elango; Matthew D. Andisik; et al. (The AAPS Journal, 2024)

Hierarchical foraging strategies of migratory short-tailed shearwaters during the non-breeding stage - Natalie Bool; Michael D. Sumner; Mary-Anne Lea; Clive R. McMahon; Mark A. Hindell (Marine Biology, 2024)
Foraging specialisations are common in animal populations, because they increase the rate at which individuals acquire food from a known and reliable source. Foraging plasticity, however, may also be important in variable or changing environments. To better understand how seabirds might respond to changing environmental conditions, we assessed how plastic the foraging behaviours of short-tailed shearwaters ( Ardenna tenuirostris ) were during their non-breeding season. To do this, we tracked 60 birds using global location sensing loggers (GLS) over a single year between 2012 and 2016 with the exception of 8 individuals that were tracked over 2 consecutive years. Birds predominantly foraged in either the Sea of Okhotsk/North Pacific Ocean (Western strategy) or the southeast Bering Sea/North Pacific (Eastern strategy). The eight birds tracked for 2 consecutive years all returned to the same core areas, indicating that these birds were faithful to foraging areas between years, although the time spent there varied, probably in response to local changes in food availability. Overall, 50% of the birds we tracked left their core area towards the end of the non-breeding period, moving into the Chukchi Sea, suggesting that the birds have flexible intra-seasonal foraging strategies whereby they follow prey aggregations. We hypothesise that seasonal declines in chlorophyll a concentrations in their primary core foraging areas coincide with changes in the availability of large-bodied krill, an important food source for short-tailed shearwaters. Decreasing prey abundance likely prompts the movement of birds out of their core foraging areas in search of food elsewhere. This strategy, through which individuals initially return to familiar areas but disperse if food is limited, provides a mechanism that allows the birds to respond to the effects of climate variability.

Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2023)
The relationships between flying Antarctic seabirds and their at-sea environments remain poorly understood, particularly outside of the breeding season. Improving our knowledge of how these marine predators use their habitat is a critical step towards conservation of these species. We tracked 27 adult Snow Petrels from two large breeding colonies in East Antarctica during the Austral winter (non-breeding period) – when they are primarily at sea away from their nesting sites. During this time, Snow Petrel habitat use was most associated with bathymetry (> 5000 m), low sea-surface height, relatively close distance to the southern boundary of the Antarctic Circumpolar Current, relatively close distance to the ice-edge, relatively high sea-ice concentration, and low sea-surface temperature. Individuals displayed various movement patterns: 20 birds occupied overlapping winter areas that ranged broadly (up to 2000 km) from their breeding sites. The remaining birds ventured far beyond their breeding sites – reaching a maximal distance from the colony of 5,268 km. One individual circumnavigated Antarctica. Daily activity patterns were related to day length, with peak activity occurring near dawn and dusk. Nocturnal activity increased from March until August/September. Key results reveal and depict Snow Petrel habitat maps for the non-breeding period in the East Antarctic region.

Opportunities and limitations of large open biodiversity occurrence databases in the context of a Marine Ecosystem Assessment of the Southern Ocean - Anne-Sophie Bonnet-Lebrun; Maxime Sweetlove; Huw J. Griffiths; Michael Sumner; Pieter Provoost; Ben Raymond; Yan Ropert-Coudert; Anton P. Van de Putte (Frontiers in Marine Science, 2023)
The Southern Ocean is a productive and biodiverse region, but it is also threatened by anthropogenic pressures. Protecting the Southern Ocean should start with well-informed Marine Ecosystem Assessments of the Southern Ocean (MEASO) being performed, a process that will require biodiversity data. In this context, open geospatial biodiversity databases such as OBIS and GBIF provide good avenues, through aggregated geo-referenced taxon locations. However, like most aggregated databases, these might suffer from sampling biases, which may hinder their usability for a MEASO. Here, we assess the quality and distribution of OBIS and GBIF data in the context of a MEASO. We found strong spatial, temporal and taxonomic biases in these data, with several biases likely emerging from the remoteness and inaccessibility of the Southern Ocean (e.g., lack of data in the dark and ice-covered winter, most data describing charismatic or well-known taxa, and most data along ship routes between research stations and neighboring continents). Our identification of sampling biases helps us provide practical recommendations for future data collection, mobilization, and analyses.

Statistical Approaches for Establishing Appropriate Immunogenicity Assay Cut Points: Impact of Sample Distribution, Sample Size, and Outlier Removal - John Garlits; Sean McAfee; Jessica-Ann Taylor; Enoch Shum; Qi Yang; Emily Nunez; Kristina Kameron; Keilah Fenech; Jacqueline Rodriguez; Albert Torri; Jihua Chen; Giane Sumner; et al. (The AAPS Journal, 2023)
The statistical assessments needed to establish anti-drug antibody (ADA) assay cut points (CPs) can be challenging for bioanalytical scientists. Poorly established CPs that are too high could potentially miss treatment emergent ADA or, when set too low, result in detection of responses that may have no clinical relevance. We evaluated 16 validation CP datasets generated with ADA assays at Regeneron’s bioanalytical laboratory and compared results obtained from different CP calculation tools. We systematically evaluated the impact of various factors on CP determination including biological and analytical variability, number of samples for capturing biological variability, outlier removal methods, and the use of parametric vs. non-parametric CP determination. In every study, biological factors were the major component of assay response variability, far outweighing the contribution from analytical variability. Non-parametric CP estimations resulted in screening positivity in drug-naïve samples closer to the targeted rate (5%) and were less impacted by skewness. Outlier removal using the boxplot method with an interquartile range (IQR) factor of 3.0 resulted in screening positivity close to the 5% targeted rate when applied to entire drug-naïve dataset. In silico analysis of CPs calculated using different sample sizes showed that using larger numbers of individuals resulted in CP estimates closer to the CP of the entire population, indicating a larger sample size (~ 150) for CP determination better represents the diversity of the study population. Finally, simpler CP calculations, such as the boxplot method performed in Excel, resulted in CPs similar to those determined using complex methods, such as random-effects ANOVA. Graphical Abstract

Pre-existing Reactivity to an IgG4 Fc-Epitope: Characterization and Mitigation of Interference in a Bridging Anti-drug Antibody Assay - Michael A. Partridge; Jihua Chen; Elif Kabuloglu Karayusuf; Thanoja Sirimanne; Colin Stefan; Ching Ha Lai; Meghna Gathani; Lisa DeStefano; Michal Rozanski; Sean McAfee; Manoj Rajadhyaksha; Matthew D. Andisik; et al. (The AAPS Journal, 2022)
Twenty percent of baseline patient samples exhibited a pre-existing response in a bridging anti-drug antibody (ADA) assay for a human IgG4 monoclonal antibody (mAb) therapeutic. In some cases, assay signals were more than 100-fold higher than background, potentially confounding detection of true treatment-emergent ADA responses. The pre-existing reactivity was mapped by competitive inhibition experiments using recombinant proteins or chimeric human mAbs with IgG4 heavy chain regions swapped for IgG1 sequences. These experiments demonstrated that the majority of the samples had reactivity to an epitope containing leucine 445 in the CH3 domain of human IgG4. The pre-existing reactivity in baseline patient samples was mitigated by replacing the ADA assay capture reagent with a version of the drug containing a wild type IgG1 proline substitution at residue 445 without impacting detection of drug-specific, treatment-emergent ADA. Finally, purification on Protein G or anti-human IgG (H + L) columns indicated the pre-existing response was likely due to immunoglobulins in patient samples. Graphical abstract

Bioanalytical Challenges due to Prior Checkpoint Inhibitor Exposure: Interference and Mitigation in Drug Concentration and Immunogenicity Assays - Andrew F. Dengler; Rachel Weiss; Tiffany Truong; Susan C. Irvin; Nidhi Gadhia; Mohamed Hassanein; Camille Georgaros; Jessica-Ann Taylor; Anne Paccaly; Giane Sumner; Matthew D. Andisik; Albert Torri; et al. (The AAPS Journal, 2021)
Monoclonal antibodies (mAbs) are a leading class of biotherapeutics. In oncology, patients often fail on early lines of biologic therapy to a specific target. Some patients may then enroll in a new clinical trial with a mAb specific for the same target. Therefore, immunoassays designed to quantify the current mAb therapy or assess immunogenicity to the drug may be susceptible to cross-reactivity or interference with residual prior biologics. The impact of two approved anti-PD-1 mAbs, pembrolizumab and nivolumab, was tested in several immunoassays for cemiplimab, another approved anti-PD-1 mAb. The methods included a target-capture drug concentration assay, a bridging anti-drug antibody (ADA) assay and a competitive ligand-binding neutralizing antibody (NAb) assay. We also tested bioanalytical strategies to mitigate cross-reactivity or interference in these assays from other anti-PD-1 biologics. Both pembrolizumab and nivolumab cross-reacted in the cemiplimab drug concentration assay. This was mitigated by addition of antibodies specific to pembrolizumab or nivolumab. ADA specific for pembrolizumab and nivolumab did not interfere in the cemiplimab ADA assay. However, pembrolizumab and nivolumab generated a false-positive response in a target-capture NAb assay. Our results demonstrate that similar exogenous pre-existing anti-PD-1 mAbs (biotherapeutics) such as pembrolizumab and nivolumab are detected and accurately quantified in the cemiplimab drug concentration assay. However, once steady state is achieved for the new therapy, prior biologics would likely not be detected. Cross-reactivity and interference in immunoassays from previous treatment with class-specific biotherapeutic(s) pose significant bioanalytical challenges, especially in immuno-oncology. Graphical abstract

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Isotyping and Semi-Quantitation of Monkey Anti-Drug Antibodies by Immunocapture Liquid Chromatography-Mass Spectrometry - Xiaoxiao Huang; Xiaobin Xu; Michael A. Partridge; Jihua Chen; Ellen Koehler-Stec; Giane Sumner; Haibo Qiu; Albert Torri; Ning Li (The AAPS Journal, 2021)
There is an urgent demand to develop new technologies to characterize immunogenicity to biotherapeutics. Here, we developed an immunocapture LC-MS assay to isotype and semi-quantify monkey anti-drug antibodies (ADAs) to fully human monoclonal antibody (mAb) drugs. ADAs were isolated from serum samples using an immunocapture step with the Fab of the full-length mAb cross-linked to magnetic beads to minimize matrix interference. A positive monoclonal antibody control against the human immunoglobulin kappa light chain was used as a calibration standard for ADA quantitation. The final LC-MS method contains 17 multiple reaction monitoring (MRM) transitions and an optimized 15-min LC method. The results suggested that IgG1 was the most abundant isotype in ADA-positive samples. IgG2 and IgG4 were identified at lower levels, whereas IgG3 and IgA levels were only observed at very minor levels. In addition, levels of total ADA measured by the LC-MS assay were comparable to results obtained using a traditional ligand binding assay (LBA). The LC-MS ADA assay enabled rapid immunogenicity assessment with additional isotype information that LBAs cannot provide.

Drug Removal Strategies in Competitive Ligand Binding Neutralizing Antibody (NAb) Assays: Highly Drug-Tolerant Methods and Interpreting Immunogenicity Data - Michael A. Partridge; Elif Kabuloglu Karayusuf; Gary Shyu; Camille Georgaros; Albert Torri; Giane Sumner (The AAPS Journal, 2020)

Morphological and molecular evidence of population divergence in a widespread shorebird across its southern mainland Australian distribution - Michael A. Weston; Kylea Clarke; Grainne S. Maguire; Joanna Sumner (Conservation Genetics, 2020)

Dispersal of an exploited demersal fish species (Argyrosomus japonicus, Sciaenidae) inferred from satellite telemetry - Thomas C. Barnes; Paul J. Rogers; Yasmin Wolf; Alessandro Madonna; Dirk Holman; Greg J. Ferguson; Wayne Hutchinson; Aude Loisier; Dylan Sortino; Michael Sumner; Bronwyn M. Gillanders (Marine Biology, 2019)

Reproductive performance and diving behaviour share a common sea‐ice concentration optimum in Adélie penguins ( Pygoscelis adeliae ) - Camille Le Guen; Akiko Kato; Ben Raymond; Christophe Barbraud; Michaël Beaulieu; Charles‐André Bost; Karine Delord; Andrew J. J. MacIntosh; Xavier Meyer; Thierry Raclot; Michael Sumner; Akinori Takahashi; et al. (Global Change Biology, 2018)
The Southern Ocean is currently experiencing major environmental changes, including in sea‐ice cover. Such changes strongly influence ecosystem structure and functioning and affect the survival and reproduction of predators such as seabirds. These effects are likely mediated by reduced availability of food resources. As such, seabirds are reliable eco‐indicators of environmental conditions in the Antarctic region. Here, based on 9 years of sea‐ice data, we found that the breeding success of Adélie penguins ( Pygoscelis adeliae ) reaches a peak at intermediate sea‐ice cover ( ca . 20%). We further examined the effects of sea‐ice conditions on the foraging activity of penguins, measured at multiple scales from individual dives to foraging trips. Analysis of temporal organisation of dives, including fractal and bout analyses, revealed an increasingly consistent behaviour during years with extensive sea‐ice cover. The relationship between several dive parameters and sea‐ice cover in the foraging area appears to be quadratic. In years of low and high sea‐ice cover, individuals adjusted their diving effort by generally diving deeper, more frequently and by resting at the surface between dives for shorter periods of time than in years with intermediate sea‐ice cover. Our study therefore suggests that sea‐ice cover is likely to affect the reproductive performance of Adélie penguins through its effects on foraging behaviour, as breeding success and most diving parameters share a common optimum. Some years, however, deviated from this general trend, suggesting that other factors (e.g. precipitation during the breeding season) might sometimes become preponderant over the sea‐ice effects on breeding and foraging performance. Our study highlights the value of monitoring fitness parameters and individual behaviour concomitantly over the long‐term to better characterize optimal environmental conditions and potential resilience of wildlife. Such an approach is crucial if we want to anticipate the effects of environmental change on Antarctic penguin populations.

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Decadal changes in habitat characteristics influence population trajectories of southern elephant seals - Mark A. Hindell; Michael Sumner; Sophie Bestley; Simon Wotherspoon; Robert G. Harcourt; Mary‐Anne Lea; Rachael Alderman; Clive R. McMahon (Global Change Biology, 2017)
Understanding divergent biological responses to climate change is important for predicting ecosystem level consequences. We use species habitat models to predict the winter foraging habitats of female southern elephant seals and investigate how changes in environmental variables within these habitats may be related to observed decreases in the Macquarie Island population. There were three main groups of seals that specialized in different ocean realms (the sub‐Antarctic, the Ross Sea and the Victoria Land Coast). The physical and climate attributes (e.g. wind strength, sea surface height, ocean current strength) varied amongst the realms and also displayed different temporal trends over the last two to four decades. Most notably, sea ice extent increased on average in the Victoria Land realm while it decreased overall in the Ross Sea realm. Using a species distribution model relating mean residence times (time spent in each 50 × 50 km grid cell) to 9 climate and physical co‐variates, we developed spatial predictions of residence time to identify the core regions used by the seals across the Southern Ocean from 120°E to 120°W. Population size at Macquarie Island was negatively correlated with ice concentration within the core habitat of seals using the Victoria Land Coast and the Ross Sea. Sea ice extent and concentration is predicted to continue to change in the Southern Ocean, having unknown consequences for the biota of the region. The proportion of Macquarie Island females (40%) utilizing the relatively stable sub‐Antarctic region, may buffer this population against longer‐term regional changes in habitat quality, but the Macquarie Island population has persistently decreased (−1.45% per annum) over seven decades indicating that environmental changes in the Antarctic are acting on the remaining 60% of the population to impose a long‐term population decline in a top Southern Ocean predator.

Development of an Analytical Method for Assessment of Silver Nanoparticle Content in Biological Matrices by Inductively Coupled Plasma Mass Spectrometry - Eric P. Poitras; Michael A. Levine; James M. Harrington; Amal S. Essader; Timothy R. Fennell; Rodney W. Snyder; Sherry L. Black; Susan S. Sumner; Keith E. Levine (Biological Trace Element Research, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

The use of OSL dating in unstructured sands: the archaeology and chronology of the Hutton Sands at Canteen Kopje (Northern Cape Province, South Africa) - Michael Chazan; Naomi Porat; T. Alexandra Sumner; Liora Kolska Horwitz (Archaeological and Anthropological Sciences, 2013)

Methods to evaluate normal rainfall for short-term wetland hydrology assessment - Jaclyn P. Sumner; Michael J. Vepraskas; Randall K. Kolka (Wetlands, 2009)

Impact of environmental conditions on the marine natural product bryostatin 1 - Thomas J. Manning; Emily Rhodes; Michael Land; Render Parkman; Brandy Sumner; TuKiet T. Lam; Alan G. Marshall¶; Dennis Phillips (Natural Product Research, 2006)

Resource partitioning through oceanic segregation of foraging juvenile southern elephant seals (Mirounga leonina) - Iain C. Field; Corey J. A. Bradshaw; Harry R. Burton; Michael D. Sumner; Mark A. Hindell (Oecologia, 2005)